O assunto do e-mail como indício de fraude: contribuições da organização da informação para a prevenção criminal - Furlaneto Neto, Mário [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In a more and more globalized and digitalized society , e-mail represents important prominence by accelerating communication among people. However, while bringing tremendous benefits to the society, Internet has also become a means by which computer crimes have been committed and, today, E-mail is used as a phase of iter criminis , which has been potentialized due to non-existence of preventive policies at all. So in this context, we try to assess the e-mail subject-field giving emphasis to the Information Organization contributions as subsidy towards preventing crimes. In this way, our purpose is to analyze the e-mail as an electronic document aiming at specifying its parts, - mainly the headlines, in which the subject is represented-, so that we may point to, on a theoretical dimension, solutions regarding criminal prevention. By means of a methodological, exploratory and descriptive approach, we start from the subject’s theoretical characterization, primarily grounded on Brazilian doctrine and jurisprudence, when e-mail’s informative, thematic and probationary dimensions are faced, in order to draw a map of e-mails received by the author and his wife so as to characterize the senders’ behavior when filling in the subject, for in their performance are matched quantification and interpretation with regard to the kind of datum to be collected , and the type of analysis . By applying concrete and process facets of the Theory of Systematic Indexation by Kaiser (1911) to the subject-field of electronic messages that were the investigation corpus, the results show signs of fraud on the emails , whose subjects were categorized as follow: a) judicial and administrative disputes; b) financial appeal (prizes, raffles, benefits, etc); c) emotional appeal; d) communication of electronic transaction (electronic trade); e) communication of electronic services; f) curiosity appeal... (Complete abstract click electronic access below)

Em uma sociedade cada vez mais globalizada e inserida digitalmente, o e-mail apresenta destaque importante, ao acelerar a comunicação entre as pessoas. No entanto, ao mesmo tempo em que a Internet revelou benefícios incomensuráveis para a sociedade tornou-se, também, um meio para a prática dos crimes informáticos e, atualmente, constata-se o emprego do e-mail como fase do iter criminis, potencializado pela ausência de uma política de prevenção. Diante desse contexto, busca-se avaliar o campo assunto do e-mail, com ênfase nas contribuições da Organização da Informação como subsídio à prevenção criminal. Com isso, objetiva-se analisar o e-mail, enquanto um documento eletrônico, visando especificar suas partições, nomeadamente a área do cabeçalho, onde consta a representação do assunto, de maneira a apontar, em uma dimensão teórica, soluções relacionadas à prevenção criminal. Por meio de uma abordagem metodológica explorativa e descritiva, parte-se de uma caracterização teórica da temática, nomeadamente na doutrina e na jurisprudência brasileira, ocasião em que são enfrentadas as dimensões informativa, temática, probatória e criminal do email, para, em seguida, realizar-se o mapeamento de e-mails recebidos pelo autor e sua esposa de modo a caracterizar como se comportam os emitentes no preenchimento do assunto, ocasião em que se combina, quanto ao tipo de dado a ser coletado e tipo de análise, quantificação com interpretação. Ao aplicarem-se as facetas concreto e processo da Teoria de Indexação Sistemática de Kaiser (1911) ao campo assunto das mensagens eletrônicas que compuseram o corpus da pesquisa, os resultados revelam indícios de fraude em e-mails cujos assuntos foram categorizados em: a) Questões/pendências judiciais e administrativas; b) Apelo financeiro (prêmios, sorteios, benefícios, etc); c) Apelo emocional;...
Keywords: Organização da informação; Mensagem de correio eletrônico; Prevenção do crime; Crimes na internet; Segurança eletrônica; Electronic message; Information Organization; Criminal prevention; Electronic safety; Crimes in Internet